The Impact of Respiratory Viral Testing in Hospitalized Adult Patients at a Tertiary Care Facility. (4th October 2017) - Ciccone, Emily; Chundi, Vahini; Miller, Melissa; DiBiase, Lauren; Weber, David; Juliano, Jonathan; Jhaveri, Ravi; Willis, Zachary; ,
Abstract: Background: The use of multiplex nucleic acid amplification assays to detect respiratory viruses is increasing. However, these tests are expensive, and the clinical significance of a positive result is often unclear. Positive viral results have the potential to decrease antibiotic use and length of stay, but their actual impact is unknown. Methods: We completed a retrospective review of all adult patients with positive respiratory viral panel (RVP; GenMark) and/or rapid RSV/influenza PCR tests (Cepheid Xpert) collected within 48 hours of admission to the general inpatient or stepdown units of an academic tertiary care hospital between September 1, 2015 and March 15, 2016. Data collected included demographics, comorbidities, clinical presentation, time of test collection and result, additional diagnostic evaluation, and antibiotic use. Results: A total of 221 positive respiratory viral tests were collected on 215 patients during the study period. The median age at time of testing was 56.8 years; 48% were female. Respiratory symptoms were documented in 92.8% of cases. COPD was the most common respiratory co-morbidity (20.2%), while 30% of patients had cancer, and 3.2% were HIV-infected. Respiratory support on admission was common (51.6%). A rapid PCR and RVP were performed in 58.8% of cases, while 28.5% had only an RVP and 12.7% had only a rapid PCR. Of the patients who had a positive rapid PCR, 17.6% also had an RVP done. Antibiotics were started within 24 hours of presentation in 87.4% of all cases and 70.6% of patients who had a positive rapid PCR. Rhinovirus was the most frequently isolated pathogen (44.6% of positive tests) followed by metapneumovirus (14%), respiratory syncytial virus (13.5%), and coronavirus (13.5%). Median time from specimen collection to result was 38.8 hours for RVP, and 15.3% were resulted after patient discharge. For those who had a rapid PCR alone, median time from collection to result was 1.5 hours. Conclusion: In this non-critically ill cohort, most patients with positive viral assays received antibiotics, and a substantial number of RVPs were resulted after discharge. This suggests that there are many lost opportunities to impact clinical management with respiratory viral testing. Disclosures: M. Miller, GenMark Diagnostics: Grant Investigator, Research support and Salary; R. Jhaveri, GenMark: Investigator, Grant recipient